Noninvasive ventilation in a young infant with congenital central hypoventilation and 7‐year follow‐up - Zhifei Xu; Yunxiao Wu; Bei Li; Li Zheng; Jingyuan Liu; Kunling Shen (Pediatric Investigation, 2019)
Abstract Introduction Congenital central hypoventilation syndrome (CCHS) is a rare disorder characterized by alveolar hypoventilation and autonomic system dysregulation secondary to mutations of the PHOX2B gene. Treatment consists of assisted ventilation using positive‐pressure ventilators via tracheostomy, bi‐level positive airway pressure (BPAP) via a noninvasive interface, negative‐pressure ventilators, or diaphragm pacing. The long‐term use of BPAP in younger children at home has been less frequently reported. Case presentation We present a case of a 2‐month‐old infant with CCHS who was successfully managed by BPAP without the need for tracheostomy and followed up for 7 years. Conclusion CCHS is a rare disease that manifests as nocturnal desaturation and carbon dioxide retention in early life. Noninvasive ventilation can be successfully used in young infants via an appropriate mask.